Combining chemical doping and thermal annealing to optimize the thermoelectric performance of the poly(3-hexylthiophene). (October 2022) - Liao, Zhixiong; Wang, Shichao; Gao, Chunmei; Wang, Lei
Abstract: Significant improvements to the thermoelectric (TE) property of doped conjugated polymeric materials have been widely investigated in recent years, and chemical doping is considered as a key to maximize the thermoelectric performance of conjugated polymers by increasing their electrical conductivity. However, chemical doping with the ability to increase the carrier concentration will reduce the order of the films, which cannot guarantee the high electrical conductivity, thus it is crucial to keep good charge transport pathways. Herein, chemical doping and thermal annealing are combined to optimize the thermoelectric property of poly(3-hexylthiophene) (P3HT). First, the doping efficiency of three dopants on P3HT was systematically investigated, among which, the film doped with FeCl3 exhibits the highest thermoelectric performance. Subsequently, thermal annealing treatment method is further applied to construct carrier pathways via improving the crystallinity orientation of the FeCl3 doped films. As a result, the electrical conductivity reaches 201.1 S cm −1, which increase by 42% in comparison with unannealed film (141.1 S cm −1 ). The optimized power factor of FeCl3 doped P3HT film is 1.72 times that of unannealed doped film and 13.0 times that of unannealed P3HT film doped by F4TCNQ. The results of this investigation demonstrate that combining chemical doping and thermal annealing is a feasible strategy to improve the thermoelectric performance of the conjugated polymer. Graphical abstract: Image 1 Highlights: The role that thermal annealing plays in reconstructing the crystalline structure. The charge carrier transport pathway is constructed via improving crystallinity. The electrical conductivity reaches 201.1 S cm −1, higher than the untreated films. The power factor increases by 68% after thermal annealing.